Cultivo de mudas de Laguncularia racemosa (L.) C. F. Gaertn com uso de águas hipersalinas e diferentes substratos - Soares, Sílvio Roberto Fernandes (2017)
The global problem regarding the degradation of mangroves encourages research aimed at maintaining or restoring this environment. In the State of Rio Grande do Norte, the saline industry, through research projects in partnership with universities, seeks a viable alternative to the use of hypersaline water, bittern, from salt production, linked to mangrove restoration projects. The goal of this study was to evaluate the quality of seedlings of Laguncularia racemosa (L.) C. F. Gaertn, 1807 produced with the use of hypersaline and low salinity water in substrate with and without coconut fiber (CF). The experiment was set up in a greenhouse at the Center of Agrarian Sciences - UFERSA – Mossoró, State of Rio Grande do Norte. The effect of three irrigation water salinity levels (A1 = 0.5 dS.m-1; A2 = 29.6 dS.m-1, A3 = 54.2 dS.m-1) was evaluated in three concentrations of substrate-restinga sand (S1= 100% AR, S2= 50%AR + 50% FC, e S3 = 75% AR + 25% CF). The experimental design was randomized blocks, 3x3 factorial arrangement, four blocks, totaling 36 plots with 25 plants in each plot. At 21, 42, 63, 84 and 105 days after the application of the treatments (DAT), analyses on the growth of seedlings included the leaf number (NF); the stem diameter (DC); plant height (AP); length of the largest root (R); dry matter of the root and shoot system (MSSR and MSPA), leaf area (AF) and unitary leaf area (AFU). With these data, we calculated the ratios e indices: root/shoot ratio (RR-PA), shoot/root ratio (RPA-R) and shoot height/stem diameter ratio (RAP-DC), total dry matter (MST), Dickson quality index (IQD) and leaf area index (LAI). Soil samples were also taken for monitoring the chemical variables of the substrate (electrical conductivity/EC, pH, Na+, K+, Ca2+, Mg2+ (t), SB and PST). At the end of the experiment, it was concluded that the addition of coconut fiber did not minimize the effect of the salts on seedling growth. The waters 0.5 dS.m-1 and 29 dS.m-1 in interaction with restinga sand substrate represented the best interactions. The interaction water with 5% (29,6 dS.m-1) hypersaline mixture plus restinga sand substrate is the most suitable for production of seedlings under the conditions of this experiment, since these would have greater capacity to adapt to the hypersaline conditions verified in mangrove ecosystems